2007
DOI: 10.1108/07378830710820989
|View full text |Cite
|
Sign up to set email alerts
|

The strategic evaluation of academic libraries

Abstract: PurposeThe purpose of this study is to analyse the network strategies of academic libraries and presents an approach to the evaluation of strategic plans and their implementation.Design/methodology/approachThe balanced scorecard approach is used as a framework for organisations to communicate and implement their strategic plans.FindingsIt is shown in this study that the balanced scorecard also provides a general framework for the evaluation of the strategy and performance from different perspectives.Practical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
2
13
0
1
Order By: Relevance
“…In this section we conduct an analysis of the data collected in the empirical investigation of Roskilde University Library and provide answers to the research questions posed in the introduction. This finding is in line with the study by Kettunen (2007) that found that libraries are developing networked cooperation with other institutions and libraries in order to develop their activities. Many innovations at RUB are thus dependent on the library management team and the employees being outgoing and alert to changes taking place elsewhere in their network.…”
Section: Analysis and Resultssupporting
confidence: 91%
“…In this section we conduct an analysis of the data collected in the empirical investigation of Roskilde University Library and provide answers to the research questions posed in the introduction. This finding is in line with the study by Kettunen (2007) that found that libraries are developing networked cooperation with other institutions and libraries in order to develop their activities. Many innovations at RUB are thus dependent on the library management team and the employees being outgoing and alert to changes taking place elsewhere in their network.…”
Section: Analysis and Resultssupporting
confidence: 91%
“…Findings related specifically to plans are limited to general observations, with more in-depth findings related to the planning process and institutional (University) alignment. Kettunen (2007) applied a balanced scorecard approach to the evaluation of strategic plans within a consortium of digital libraries across 29 Finnish universities, but at a high level based on four perspectives (customer, finance, internal processes, and learning), and focused on implementation. Methodology is only provided in overview, and evaluation limited to general observations.…”
Section: Methodological Approach To Evaluationmentioning
confidence: 99%
“…Relatos das aplicações destas iniciativas têm sido realizados em diversos países como China, Estados Unidos, Reino Unido, Suíça, Paquistão, Alemanha, Coréia (CHO; KORTE, 2014), dentre inúmeros outros. A abordagem clássica do BSC em suas quatro perspectivas: financeira, cliente, processos internos e aprendizado e crescimento têm conseguido melhorar as ações empresariais com base em sua estratégia de negócios (PIENAAR; PENZHORN, 2000;KETTUNEN, 2007;MANSOORI;TAHERIDEMNE;MONFARED, 2012).…”
Section: Introductionunclassified